Fostering a Creative Economy to Drive Korean Growth - Jones, Randall S.. (OECD Publishing, 2014)
A creative economy requires innovation-friendly conditions. Korea's innovation system should be improved by upgrading universities and expanding their role in business R&D, while increasing international collaboration in R&D from its current low level. The returns from Korea's large investment in innovation should be enhanced by improving framework conditions - easing product market regulations, promoting international competition and enhancing labour market flexibility - to encourage the adoption of new technology. Venture businesses and start-ups should play a key role in commercialising innovation. To make venture investment a growth driver, it is important to expand the role of business angels, activate the merger-and-acquisition market and foster entrepreneurship. A creative economy also depends on making SMEs, which account for 87% of employment, more dynamic. SME policies should be streamlined and improved to promote market-based financing and reduce the negative effects of government funding programmes, which discourage the expansion of SMEs. The growth of small firms also depends on resolving labour market mismatches and taking full advantage of the opportunities afforded by the Internet. This Working Paper relates to the 2014 OECD Economic Survey of Korea (www.oecd.org/eco/economic-survey-korea.htm)
Keywords: Economics; Industry and Services; Korea, Republic of